EKSPLORASI LINGKUNGAN SEKOLAH UNTUK MENINGKATKAN PENGETAHUAN SAINS ANAK USIA DINI - Endah Nurliana Sapitri; Sukarno; Samsu (Al Hanin, 2026)
conducted in two cycles involving early childhood learners. Data were collected through observation and documentation. The results show an improvement in children’s science understanding from Cycle I to Cycle II. In Cycle I, children’s participation and understanding were categorized as moderate, while in Cycle II, there was a significant improvement indicated by increased curiosity, active participation, and better ability to identify differences in plant shape, color, and size. The learning process became more interactive and meaningful as children directly engaged with real objects in their environment. This study contributes to early childhood science learning by providing evidence that environmental exploration is an effective experiential learning strategy to enhance children’s cognitive development in understanding basic scientific concepts in a concrete and meaningful way.